SOCIALIZATION OF THE USE OF SCREEN PRINTING MACHINES AS A SUPPORTING TOOL FOR MAKING SOUVENIRS AT THE MANGROVE BEACH OF KAMPUNG NIPAH - Sukma Hayati Hakim; Raina Linda Sari; Coki Ahmad Syahwier; Syech Suhaimi (RADJA PUBLIKA, 2023)
This community service aims to empower the community in Sei Nagalawan Village, Kampung Nipah, through training in the use of digital printing machines. This village faces economic challenges due to the limited availability of souvenirs that can be produced consistently and the underwhelming income from the tourism sector. The service team introduced digital printing machines and provided training on material selection to enhance the production of souvenirs, such as t-shirts and merchandise. The training results indicated that participants successfully acquired new skills and improved product quality, although challenges in the availability of raw materials remain. Future plans include product development and exploration of new marketing opportunities to increase community income through digital platforms.